2011
DOI: 10.1371/journal.pgen.1002281
|View full text |Cite
|
Sign up to set email alerts
|

The Receptor Tyrosine Kinase Alk Controls Neurofibromin Functions in Drosophila Growth and Learning

Abstract: Anaplastic Lymphoma Kinase (Alk) is a Receptor Tyrosine Kinase (RTK) activated in several cancers, but with largely unknown physiological functions. We report two unexpected roles for the Drosophila ortholog dAlk, in body size determination and associative learning. Remarkably, reducing neuronal dAlk activity increased body size and enhanced associative learning, suggesting that its activation is inhibitory in both processes. Consistently, dAlk activation reduced body size and caused learning deficits resembli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

12
134
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 95 publications
(146 citation statements)
references
References 66 publications
12
134
0
Order By: Relevance
“…Results of the second study, suggested a decreased anxiety for Alk mutants and an increased performance in spatial memory. Interestingly, this phenotype is consistent with the one described in Drosophila , since dAlk inhibition was shown to enhance olfactory associative learning in this model organism [15]. It therefore appears that whereas Alk inhibition decreases anxiety in mice, Alk activation induces an opposite effect.…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…Results of the second study, suggested a decreased anxiety for Alk mutants and an increased performance in spatial memory. Interestingly, this phenotype is consistent with the one described in Drosophila , since dAlk inhibition was shown to enhance olfactory associative learning in this model organism [15]. It therefore appears that whereas Alk inhibition decreases anxiety in mice, Alk activation induces an opposite effect.…”
Section: Discussionsupporting
confidence: 88%
“…Drosophila embryos lacking dALK die due to abnormalities in the formation of gut musculature [13] and the dALK receptor is also involved in the neuronal circuit assembly of the visual system [14]. More recently, it has been shown that dALK plays critical roles in body size determination and associative olfactory learning [15] and that it permits central nervous system (CNS) growth under nutrient restriction [16]. In contrast to Drosophila , mice deficient in Alk are viable, fertile and display a normal appearance [17,18].…”
Section: Introductionmentioning
confidence: 99%
“…Nf1 +/− mice have higher levels of phosphorylated ERK in the brain and basal GABA release (Cui et al, 2008; Repunte-Canonigo et al, 2015), also similar to what we found in Alk −/− mice. In Drosophila , genetic or pharmacological inhibition of Alk rescues the increased ERK activation and associative learning deficits observed in Nf1 mutants (Gouzi et al, 2011), suggesting that ALK and NF1 function in the same intracellular signaling pathway. These results, combined with the human genetic association studies that implicate the NF1 and ALK genes in alcohol dependence (Repunte-Canonigo et al, 2015; Wang et al, 2011), support the possibility that ALK may play an active role in dependence-induced drinking through regulation of the Ras/ERK signaling pathway.…”
Section: Discussionmentioning
confidence: 99%
“…By contrast, activation of the KIT receptor by stem cell factor (also known as KIT ligand) has a key role in neurofibroma formation in mice 62 . In Drosophila melanogaster expressing mutant Nf1 , the loss of the receptor tyrosine kinase Anaplastic lymphoma kinase (Alk) rescues the small size of the flies and ERK activation 84 . Other receptors probably function as upstream regulators of neurofibromin in specific cell types.…”
Section: Neurofibromin Regulation and Signallingmentioning
confidence: 99%